Lao People's Democratic Republic : Poverty Reduction Strategy Paper; Annual Progress Report. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This Annual Progress Report (APR) reviews the Poverty Reduction Strategy Paper for Lao People's Democratic Republic (PDR). Noticeable improvements have also occurred in many economic, social, institutional, and legal development areas. While strengthening the management of the public sector and governance, the GoL is increasing public investment to develop physical and social infrastructure and promote human resources. The promotion of the private sector is receiving greater attention through significant improvements in the business climate and trade facilitation. Macroeconomic indicators are also evolving in a satisfactorily manner.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet